Short-term effect of ambient air pollution on outpatient visits for children in Guangzhou, China - Chen, Sili; Xu, Binhe; Shi, Tongxing; Yang, Qiaoyuan (Frontiers in Public Health, 2023)
This study examined the short-term relationship between ambient air pollutants and children’s outpatient visits, and identified the effect of modifications by season. Daily recordings of air pollutants (CO, NO2, O3, SO2, PM10, and PM2.5) and children’s outpatient visit data were collected in Guangzhou from 2015 to 2019. A generalized additive model adjusted for potential confounding was introduced to verify the association between ambient air pollution and outpatient visits for children. Subgroup analysis by season was performed to evaluate the potential effects. A total of 5,483,014 children’s outpatient visits were recorded. The results showed that a 10 μg/m3 increase in CO, NO2, O3, SO2, PM10, and PM2.5 corresponded with a 0.19% (95% CI:0.15–0.24%), 2.46% (2.00–2.92%), 0.27% (0.07–0.46%), 7.16% (4.80–9.57%), 1.16% (0.83–1.49%), and 1.35% (0.88–1.82%) increase in children’s outpatient visits on the lag0 of exposure, respectively. The relationships were stronger for O3, PM10, and PM2.5 in the warm seasons, and for CO, NO2, and SO2 in the cool seasons. When adjusting for the co-pollutants, the effects of CO, NO2, and PM10 were robust. The results of this study indicate that six air pollutants might increase the risk of children’s outpatient visits in Guangzhou, China, especially in the cool season.